Corporate credit and leverage in the EU: Recent evolution, main drivers and financial stability implications - Thorsten Beck; Tuomo Peltonen; Enrico C. Perotti; Antonio Sánchez Serrano; Javier Suárez (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2023)
This report presents a long-term view of the evolution of financing of EU non-financial corporations (NFCs) in recent decades. It finds a decline in NFC leverage since at least 2008, and across countries, size categories and industries. It also documents a growing role of non-bank financial intermediaries in the provision of credit to NFCs. After exploring supply and demand drivers of the observed evolution, the report considers potential general equilibrium outcomes in terms of a reallocation of credit to other sectors or assets. This could generate greater systemic risk through unsustainable valuations or exposures to more highly correlated negative shocks. The report also stresses the urgency of developing a comprehensive macroprudential framework for non-bank financial intermediaries and calls macroprudential authorities to closely monitor the NFC sector.
Keywords: 330; credit; debt capital; capital structure; corporate bond; informal financial sector; financial crisis; financial market supervision; EU countries; Kredit; Fremdkapital; Kapitalstruktur; Unternehmensanleihe; Informeller Finanzsektor; Finanzkrise; Finanzmarktaufsicht; EU-Staaten